Current Account Imbalances : Can Structural Policies Make a Difference? - Ivanova, Anna (IMF Working Papers; Working Paper, 2012)
The discussion of global and regional imbalances has put the spotlight on the possible link between current accounts and structural policies. Drawing on standard empirical current account models, the paper finds that the commonly recommended structural factors cannot explain the widening of imbalances prior to the 2008 - 09 crisis. That said, structural factors do help explain some part of long-standing cross-country differences in the current account levels. In particular, countries with stricter credit market regulation, higher taxes on businesses, lower minimum wage (in particular,in slow growing economies) and generous unemployment benefits tend to have higher current account balances than others.